2003
DOI: 10.1016/s0092-8674(03)00234-4
|View full text |Cite
|
Sign up to set email alerts
|

MTA3, a Mi-2/NuRD Complex Subunit, Regulates an Invasive Growth Pathway in Breast Cancer

Abstract: Estrogen receptor is a key regulator of proliferation and differentiation in mammary epithelia and represents a crucial prognostic indicator and therapeutic target in breast cancer. Mechanistically, estrogen receptor induces changes in gene expression through direct gene activation and also through the biological functions of target loci. Here, we identify the product of human MTA3 as an estrogen-dependent component of the Mi-2/NuRD transcriptional corepressor in breast epithelial cells and demonstrate that MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
493
4
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(522 citation statements)
references
References 47 publications
22
493
4
3
Order By: Relevance
“…Understanding the mechanisms involved in the regulation of Snail and other E-cadherin repressors is an important issue to advance in our understanding of the tumor invasion process. Recently it was reported that the Mi-2/NuRD corepressor complex is involved in the transcriptional repression of Snail in an estrogen receptor-dependent fashion in breast cancer cells (18). This information suggests additional levels of regulation for the Snail-mediated repression of E-cadherin, involving the participation of at least two corepressor complexes.…”
Section: Vol 24 2004mentioning
confidence: 98%
“…Understanding the mechanisms involved in the regulation of Snail and other E-cadherin repressors is an important issue to advance in our understanding of the tumor invasion process. Recently it was reported that the Mi-2/NuRD corepressor complex is involved in the transcriptional repression of Snail in an estrogen receptor-dependent fashion in breast cancer cells (18). This information suggests additional levels of regulation for the Snail-mediated repression of E-cadherin, involving the participation of at least two corepressor complexes.…”
Section: Vol 24 2004mentioning
confidence: 98%
“…Metastasis-associated gene 1 overexpression is associated with the most malignant behaviour in several human tumours. Metastasisassociated gene 3 has a predominant role in lymphoma and breast cancer, in the latter leading to aberrant expression of the transcriptional repressor Snail and loss of expression of the celladhesion molecule E-cadherin, an event associated with invasive growth of breast cancers (Fujita et al, 2003).…”
Section: Genes Mediating the Disruption Of Chromatin Remodellingmentioning
confidence: 99%
“…Plasmacytoid dendritic cells, totaling 5 Â 10 6 were isolated using the MACS separation and monoclonal anti-BDCA-2 (Miltenyi Biotec). RNA was purified 24 followed by reverse transcription using the gene specific oligonucleotide primer, BDCA-2-R (5 0 -CTCGAGTATG TAGATCTTCT TCATCTT-3 0 ). Specific PCR employed primers BDCA-2-F (5 0 -CATATGGTGC CTGAAGAAGA GC-3 0 ) and BDCA-2-R. DNA sequencing confirmed the correct full-length coding region, 20 which was subcloned into the mammalian expression vector pcDNA3.1 þ (Invitrogen) to generate pFL.BDCA-2.…”
Section: Cloning and Expression Of Human Bdca-2mentioning
confidence: 99%